Kaposi's sarcoma associated herpesvirus tegument protein ORF75 is essential for viral lytic replication and plays a critical role in the antagonization of ND10-instituted intrinsic immunity - Full, Florian; Jungnickl, Doris; Reuter, Nina; Bogner, Elke; Brulois, Kevin; Scholz, Brigitte; Stürzl, Michael; Myoung, Jinjong; Jung, Jae U.; Stamminger, Thomas; Enßer, Armin (PLoS Pathogens, 2014)
Nuclear domain 10 (ND10) components are restriction factors that inhibit herpesviral replication. Effector proteins of different herpesviruses can antagonize this restriction by a variety of strategies, including degradation or relocalization of ND10 proteins. We investigated the interplay of Kaposi's Sarcoma-Associated Herpesvirus (KSHV) infection and cellular defense by nuclear domain 10 (ND10) components. Knock-down experiments in primary human cells show that KSHV-infection is restricted by the ND10 components PML and Sp100, but not by ATRX. After KSHV infection, ATRX is efficiently depleted and Daxx is dispersed from ND10, indicating that these two ND10 components can be antagonized by KSHV. We then identified the ORF75 tegument protein of KSHV as the viral factor that induces the disappearance of ATRX and relocalization of Daxx. ORF75 belongs to a viral protein family (viral FGARATs) that has homologous proteins in all gamma-herpesviruses. Isolated expression of ORF75 in primary cells induces a relocalization of PML and dispersal of Sp100, indicating that this viral effector protein is able to influence multiple ND10 components. Moreover, by constructing a KSHV mutant harboring a stop codon at the beginning of ORF75, we could demonstrate that ORF75 is absolutely essential for viral replication and the initiation of viral immediate-early gene expression. Using recombinant viruses either carrying Flag- or YFP-tagged variants of ORF75, we could further corroborate the role of ORF75 in the antagonization of ND10-mediated intrinsic immunity, and show that it is independent of the PML antagonist vIRF3. Members of the viral FGARAT family target different ND10 components, suggesting that the ND10 targets of viral FGARAT proteins have diversified during evolution. We assume that overcoming ND10 intrinsic defense constitutes a critical event in the replication of all herpesviruses; on the other hand, restriction of herpesviral replication by ND10 components may also promote latency as the default outcome of infection.
EVALuna2:8222